2022
DOI: 10.1109/ojcs.2022.3188249
|View full text |Cite
|
Sign up to set email alerts
|

Fusing Blockchain and AI With Metaverse: A Survey

Abstract: Metaverse as the latest buzzword has attracted great attention from both industry and academia. Metaverse seamlessly integrates the real world with the virtual world and allows avatars to carry out rich activities including creation, display, entertainment, social networking, and trading. Thus, it is promising to build an exciting digital world and to transform a better physical world through the exploration of the metaverse. In this survey, we dive into the metaverse by discussing how Blockchain and Artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(174 citation statements)
references
References 88 publications
(77 reference statements)
0
97
0
Order By: Relevance
“…As metaverse research increases, several studies have discussed the security of metaverse environments [17]- [21]. In 2016, O'Brolchain et al [17] claimed that privacy threats are possible in virtual reality because users perform many tasks and activities in virtual spaces, and user data are frequently communicated with servers and other users through public channels.…”
Section: Related Workmentioning
confidence: 99%
“…As metaverse research increases, several studies have discussed the security of metaverse environments [17]- [21]. In 2016, O'Brolchain et al [17] claimed that privacy threats are possible in virtual reality because users perform many tasks and activities in virtual spaces, and user data are frequently communicated with servers and other users through public channels.…”
Section: Related Workmentioning
confidence: 99%
“…In another study conducted by Ynag et al (2022), it is shown that Metaverse can be incorporated with other data-driven technologies (e.g., AI and blockchain) to develop a metaverse economy. This idea stems from the view that Metaverse can be considered as a full and self-contained economic system, with the ability to carry out digital production-based economic operations (i.e., creation, exchange, and consumption).…”
Section: Metaversementioning
confidence: 99%
“…Metaverse is a virtual medium with blockchain innovations that ensures data privacy [4]. Many companies and organizations have recently invested in the metaverse [5][6]. As the metaverse became more popular, transportation needs grew.…”
Section: Introductionmentioning
confidence: 99%